Rodar filmes, fazer cinema: Alexandre Robatto filho e as imagens dos povos - Ana Luisa de Castro Coimbra (2019)
This research traces the filmography of a Bahia’s director Alexandre Robatto Filho with the objective of noting how people appear in the images and how different cinematographic treatments are operated for these apparitions to happen. We understand that his films, whether by order for others or personal produtions, have put images and imaginaries about Bahia, but especially of his people, helping to forge through the cinema a kind of inonlyventory of popular figures, even when the primordial intention was not to portray them. This presences on screen - that shines or flashes - emanate a power leading not to a critical and analytical look at the work of Alexandre Robatto Filho, since, from these apparitions, we put in dialogue other works cinematographic and visual.